2013
DOI: 10.5558/tfc2013-113
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear multivariate modeling of strand mechanical properties with near-infrared spectroscopy

Abstract: The purpose of this research was to determine if nonlinear calibrations of near-infrared spectra could improve the prediction of strand mechanical properties. Strands similar in dimension to strands utilized in an oriented strand board composite process were prepared and tested for mechanical properties in three-point bending and then calibrated to near-infrared reflectance spectroscopy. It was found that an additional 7% to 16% of the variation in mechanical properties could be accounted for when second-and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For example, in juvenile wood from Pinus palustris, when the microfibril angle exceeded ca 30°, the plastic deformation in the lignin matrix became significant in the contribution to rupture. 26 When principal component non-linear regression was utilised to model the modulus of rupture, hemicelluloseassociated wavelengths in the near infrared region were found to be significant for prediction, 27 as it has been found that xylose is tightly bound to the cellulose microfibrils even after partial hydrolysis. 28 Xylose would thus be important in the transfer of stress between cellulose fibrils, with more xylose along the glucose chain equating to a more uniform stress distribution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in juvenile wood from Pinus palustris, when the microfibril angle exceeded ca 30°, the plastic deformation in the lignin matrix became significant in the contribution to rupture. 26 When principal component non-linear regression was utilised to model the modulus of rupture, hemicelluloseassociated wavelengths in the near infrared region were found to be significant for prediction, 27 as it has been found that xylose is tightly bound to the cellulose microfibrils even after partial hydrolysis. 28 Xylose would thus be important in the transfer of stress between cellulose fibrils, with more xylose along the glucose chain equating to a more uniform stress distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the predictive capacity of the NIR model has been the focus of discussion with partial least squares (PLS) working better than principal components regression (PCR) for improved r 2 and other predictive diagnostics. However, more and more scientists are using the coefficients/loadings within the models to interpret the relationship between wood chemistry functional groups and key traits including tensile strength [ 23 , 24 ], bending [ 11 , 25 ], calorific content [ 26 ], among others. But currently, it is unknown if PLS loading plots are statistically similar to that obtained from PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Structural water; associated with starch or cellulose(140,141) and other polymers(106,142,143), associated with sugars(142,(144)(145)(146), associated with proteins(147) or amino compounds(148), associated with membrane structure, influenced by temperature(117), related to mechanical properties(106), indicator of fermentation(149), indicative of vegetative growth stage(142), indicator of crystallinity(118, 150), indicator of preservation of tissues, damage(113) Currently available information and the tentative functionality of corresponding water species in biological and aqueous systems.…”
mentioning
confidence: 99%